2008 34th Annual Conference of IEEE Industrial Electronics 2008
DOI: 10.1109/iecon.2008.4758299
|View full text |Cite
|
Sign up to set email alerts
|

Power maximization and voltage sag/swell ride-through capability of PMSG based variable speed wind energy conversion system

Abstract: The increasing penetration level of wind farms in power system network requires better understanding of shortterm voltage stability and ride through capability before their interconnection to grid. The future wind turbines must stay connected irrespective of any type of disturbance in grid. To achieve reliable operation and control, the wind turbines must be actively controlled in order to meet the stringent grid interconnection requirements. This paper presents the modeling and performance analysis of wind en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…To verify the proposed control technique to achieve multiobjectives for grid interfaced DG systems [8], [9] connected to a 3-phase 4-wire network, an extensive simulation study is carried out using MATLAB/Simulink as shown in Fig.4.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…To verify the proposed control technique to achieve multiobjectives for grid interfaced DG systems [8], [9] connected to a 3-phase 4-wire network, an extensive simulation study is carried out using MATLAB/Simulink as shown in Fig.4.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The wind conversion system used in this study is based on permanent magnet synchronous generator (PMSG) and three phase rectifier converter which is connected to the dc bus [27], [28]. The power captured by the wind turbine (power delivered by rotor) is given by equation 11:…”
Section: Wind Conversion Systemmentioning
confidence: 99%
“…Later, they have become some of main sources. The utility is concerned due to the high penetration level of intermittent Wind energy system in distribution systems as it may pose a threat to network in terms of stability, voltage regulation and power-quality (PQ) issues at PCC [1,2].…”
Section: Introductionmentioning
confidence: 99%